Compliance of Medical Personnel Against the Implementation of Informed Consent: A Lawsuit Prevention Study for Medical Disputes - Etyn Ariyani Susilowati; Wardah Yuspin; Absori Absori (SOEPRA, 2021)
Abstract: Humans are social creatures, namely creatures that require interaction with other humans. Interaction between humans is not only communication but involves all aspects of life, including the legal aspect. Based on law number 36 of 2014 concerning health workers, it is anyone who devotes himself to the health sector and has knowledge and/or skills through education in the health sector which for certain types requires the authority to carry out health efforts. The purpose of this study was to determine the level of compliance of medical personnel in the implementation of informed consent. In addition, medical personnel understand the role of informed consent in preventing lawsuits and medical disputes. The research method used is a non-doctrinal research method, namely the questionnaire method, direct interviews with medical personnel, and medical record documents, especially informed consent sheets. Problem formulation: 1. How is the compliance of medical personnel with the implementation of informed consent? 2. What is the role of Informed Consent in Medical Dispute Prevention efforts? 3. What is the concept of implementing informed consent in order to prevent medical disputes? The results of the study: "Medical Personnel Compliance with the Implementation of Informed Consent: Study on Prevention of Lawsuits for Medical Disputes at the Central Surgical Installation of PKU Muhammadiyah Sragen Hospital" is that the compliance of medical personnel in the implementation of informed consent has not been carried out in accordance with the existing SOPs, so the role of informed consent consent has not been maximally implemented by medical personnel. The concept of implementing informed consent must be made clearly in accordance with standard procedures that must be filled in completely by medical personnel working in the central surgical installation of PKU Muhammadiyah Hospital Sragen.Keywords: Medical Personnel, Informed Consent, Lawsuits, Medical Disputes.Abstrak: Manusia merupakan makhluk sosial, yaitu makhluk yang  membutuhkan interaksi dengan manusia lainnya. Interaksi antar manusia tidak hanya komunikasi saja tetapi menyangkut seluruh aspek kehidupan, tidak terkecuali aspek hukum. Berdasarkan undang undang nomor 36 tahun 2014 tentang tenaga kesehatan adalah setiap orang yang mengabdikan diri dalam bidang kesehatan serta memiliki pengetahuan dan/atau keterampilan melalui pendidikan di bidang kesehatan yang untuk jenis tertentu memerlukan kewenangan untuk melakukan upaya kesehatan.Tujuan dari penelitian ini adalah untuk mengetahui tingkat kepatuhan tenaga medis dalam pelaksanaan informed consent. Selain itu juga sebagai pemahaman tenaga medis atas peran dari informed consent dalam upaya pencegahan gugatan hukum dan sengketa medis.Metode penelitian yang digunakan adalah metode penelitian Non-Doktrinal yaitu dengan metode quesioner, wawancara langsung kepada tenaga medis, dan dokumen rekam medis, khususnya lembar informed consent.Perumusan Masalah: 1. Bagaimana Kepatuhan Tenaga Medis Terhadap Pelaksanaan Informed  Consent ? 2. Apa peran Informed Consent dalam upaya Pencegahan Sengketa Medis? 3. Bagaimana konsep tentang pelaksanaan informed consent  dalam  rangka mencegah sengketa medis?Hasil Penelitian : “Kepatuhan Tenaga Medis Terhadap Pelaksanaan Informed Consent : Studi Pencegahan Gugatan Hukum atas Sengketa Medis di Instalasi bedah sentral RSU PKU Muhammadiyah Sragen” adalah bahwa kepatuhan tenaga medis dalam pelaksanaan informed consent, belum dilaksanakan sesuai dengan SOP yang ada, sehingga peran dari informed consent belum maksimal dilaksanakan oleh tenaga medis. Konsep pelaksanaan informed consent harus dibuat secara jelas sesuai dengan standart prosedur yang harus di isi lengkap oleh tenaga medis yang bekerja di Instalasi bedah sentral RSU PKU Muhammadiyah Sragen.Kata Kunci : Tenaga Medis, Informed Consent, Gugatan Hukum, Sengketa Medis.